Evolution of natrocarbonatite from a wollastonite nephelinite parent: Evidence from the June, 1993 eruption of Oldoinyo Lengai, Tanzania - Dawson, J; Pyle, D; Pinkerton, H (1996)
Lapilli and unusually thick, high viscosity lavas extruded from Oldoinyo Lengai in June, 1993 are composed of crystal-rich natrocarbonatite containing a small proportion of porphyritic silicate spheroids. The silicate spheroids are of wollastonite nephelinite mineralogy, but they also contain natrocarbonatite mineral grains and aggregates (a) in glass inclusions within nepheline and pyroxene phenocrysts, and (b) within the fine-grained silicate groundmass of the spheroids. The chemical relationships of the natrocarbonatite component in the spheroids to the dominant silicate fraction are consistent with liquid immiscibility, as are the multiple stages of unmixing. These direct observations confirm the intimate relationship between natrocarbonatite and wollastonite nephelinite inferred both from the field relationships at Oldoinyo Lengai, and from low-PT experimentation. The plutonic equivalent (wollastonite ijolite) of the magma type found to be parental to natrocarbonatite at Oldoinyo Lengai does occur in other carbonatite complexes of differing ages and wide geographical distribution; hence it is possible that the generation of natrocarbonatite is not unique to Oldoinyo Lengai. Certain features in the matrix of the carbonatite flows (coarser grain size, breakdown of solid-solutions observed in earlier, rapidly chilled lavas) are attributed to the relatively slow cooling of these atypically thick flows.